Regenerative medicine in orthopedics - Maj, Agnieszka Paula; Dobrowoska-Czopor, Barbara (Journal of Education, Health and Sport, 2019)
Regenerative medicine is an interdisciplinary field of science that has been experiencing its renaissance in recent years. It involves many hopes regarding the possibility of breeding the organ needed for transplantation for a given patient in laboratory conditions. The most important "component" in regenerative medicine are stem cells and other elements that create an ideal environment for their proper development and organization of tissue architecture.